Implementasi Akuntansi Menggunakan Aplikasi MYOB Accounting untuk Menyelesaikan Transaksi Keuangan pada CV Budproject Surabaya - Ferdian Nur Ammelia; Lis Setyowati (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study aims to apply the implementation of accounting using the MYOB Accounting application in the settlement of financial transactions that occur in CV. Budproject Surabaya. The data studied are in the form of financial transactions that occur in CV. Budproject Surabaya. Data collection techniques used are observation techniques, literature studies, and document studies. The analysis technique used is data collection, data reduction, and data presentation. The results of this study indicate that the implementation of accounting using the MYOB Accounting application is very effectively applied in CV. Budproject Surabaya. The effectiveness of computerized accounting MYOB Accounting is able to provide financial report output quickly and accurately.